SYNCHRONOUS PRIMARY HYPERPARATHYROIDISM AND PAPILLARY THYROID CANCER, INITIALLY PRESENTING WITH RECURRENT CHEST PAIN - Bahrudin, Mohd Fyzal; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND The coexistence of primary hyperparathyroidism (pHPT) and thyroid disease is well recognized, but the simultaneous occurrence of pHPT due to parathyroid hyperplasia and thyroid malignancy, particularly papillary thyroid carcinoma (PTC), is rare. We present a unique case of a 46-year-old female diagnosed with pHPT due to parathyroid hyperplasia and concurrent PTC affecting both thyroid lobes. CASE A 46-year-old female had recurrent chest pain and was evaluated by cardiology in a district hospital from 2021 to May 2024. Persistent hypercalcemia, unnoticed initially, was later identified. An exercise stress test was inconclusive, and a CT coronary angiogram showed no coronary stenosis or plaque, with a total calcium score of 0. Moderate hypercalcemia prompted referral to endocrinology. Laboratory investigations revealed elevated corrected calcium (3.01 mmol/L), low phosphate (0.73 mmol/L), elevated intact parathyroid hormone (iPTH) (197 pg/mL), normal alkaline phosphatase (138 U/L), and low 25-hydroxy vitamin D₃ (33 nmol/L), suggestive of PTH-mediated hypercalcemia. A 24-hour urine calcium-creatinine ratio was low, likely due to vitamin D deficiency. Thyroid function tests were normal. Neck ultrasound identified bilateral thyroid nodules, including a highly suspicious left-sided nodule (TIRADS 5). Technetium (⁹⁹mTc) sestamibi scintigraphy demonstrated a parathyroid adenoma (0.9 × 0.8 × 2.7 cm) infero-posterior to the lower pole of the left thyroid gland. Fine-needle aspiration biopsy of the thyroid nodule was suspicious for PTC. Further imaging revealed right nephrolithiasis, and a DEXA scan indicated severe osteoporosis (T-score: -3.7 at L4). The patient underwent total thyroidectomy with left inferior parathyroidectomy and central neck lymph node dissection in October 2024. Histopathology confirmed PTC in a background of nodular hyperplasia (TNM staging: pT1b pN1a). The left inferior parathyroid gland showed hyperplasia. Postoperatively, the patient was chest pain-free and is currently on cholecalciferol with calcium carbonate supplementation. CONCLUSION Recognizing chest pain in the setting of PTH-mediated hypercalcemia is crucial to prevent complications of chronic hypercalcemia and avoid unnecessary cardiac investigations. This case underscores the need for thorough endocrine and metabolic evaluations in patients presenting with persistent hypercalcemia and chest pain.